Optimised PLGA–fucoidan–PDMS composite scaffolds for bone tissue engineering: Improved mechanical and structural performance - Kamal, Izdihar; Mohd Hapipi, Nurhidayah; Mohd Zaid, Mohd Hafiz; Khairul, Nazathul Syazliyana; Abdul Ghani, Norshazliza; Loh, Zhi Wei; Saharuddin, Nur Zawani; Abdul Jamil, Aminatul Saadiah; Mohammad Diah, Hatikahaty; Abdul Hamid, Khairiah; Abdul Karim, Muhammad Khalis (Springer Nature, 2025)
The advancement of tissue engineering relies on the development of scaffolds with optimal mechanical stability, controlled degradation rates, and good cell development. This study focuses on fabricating and evaluating composite fucoidan with poly(lactic-co-glyco acid) (PLGA) and polydimethylsiloxane (PDMS). The materials were selected for their specific properties, with fucoidan providing hydrophilicity and biological properties, PLGA for mechanical strength and biodegradability, and PDMS offering flexibility and biocompatibility. Four scaffold samples were prepared by varying PLGA, fucoidan, and hydrogen silicon (HS) concentrations while maintaining PDMS at a constant 80%. Structural analysis of the fabricated scaffolds was conducted using X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM). Meanwhile, mechanical properties like compression strength and elasticity were tested using compression testing. The scaffolds of PLGA-fucoidan-PDMS have a highly porous structure with interconnected pores for cell adhesion and proliferation. Structural integrity was maintained under physiological conditions, and the compression strength and elasticity were good. In addition, the composite ratios can be adjusted to obtain a degradation rate of the scaffolds that are sufficiently low to permit the complete integration of surrounding tissues while maintaining the support of scaffolds. Sample 4 (PLGA: 5%, fucoidan: 2.5%, HS: 12.5%) showed the most promising results, with a compressive strength of 4.60 MPa, a rough and porous surface, and good mechanical stability, making it well-suited for bone tissue engineering applications.